Correlation analysis between morphologic characteristics of the thoracolumbar basivertebral foramen and Kummell’s disease in patients with osteoporosis using imaging techniques - Guang bing Qin; Yi Hua Wu; Huan Shi Chen; Yu Ting Huang; Jun Fei Yi; Ying Xiao (BMC Musculoskeletal Disorders, 2023)
Abstract Background The aging of the population is a social problem faced by many countries in the world. With the increase in the elderly population, the number of patients with Kummell’s disease is also gradually increasing. No study has demonstrated that Kummell’s disease has a clear correlation with the foramen of a vertebrobasilar vein. Objectives The research was conducted to describe and evaluate the morphological characteristics of a basivertebral foramen in patients with osteoporosis and Kummell’s disease by CT; to infer whether the specific morphological characteristics of basivertebral foramen may be one of the risk factors of Kummell’s disease; to provide clinical suggestions for the treatment of Kummell’s disease. Design Retrospective analysis from January 2020 to December 2021 on 83 patients with 83 vertebral bodies (T8-L5) diagnosed with senile osteoporosis and Kummell’s disease hospitalized in our hospital due to chronic low back pain, including 57 women and 23 men. Group A was assigned for the following patients: the age ranged from 59 to 86 years old, with the average age of 67.30 ± 7.32 years old; the body mass index ranged from 20.01 to 29.46 kg/m2, with the average body mass index of 23.51 ± 3.03 kg/m2.Group B was assigned for the following patients: 83 patients diagnosed with senile osteoporosis in our outpatient department from January 2020 to December 2021, including 41 males and 42 females; the age ranged from 60 to 85 years, with an average age of 68.52 ± 4.68 years old; the height to weight ratio met the normal reference standard (except 20% above or 10% below the standard weight). Through the lanwon PACS imaging system, the related parameters of the vertebrobasilar foramen in patients with osteoporosis and Kummell’s disease were measured to evaluate and analyze the correlation between the morphological characteristics of the vertebrobasilar foramen in patients with osteoporosis and Kummell’s disease. Results In patients with osteoporosis, the distribution of incidence rate of Kummell’s disease in the spine was consistent with that of osteoporotic compression fractures. Sagittal view of the vertebral body on CT scan and the triangular-shaped, trapezoidal-shaped, and irregular-shaped basivertebral foramen in group A accounted for 18%,57%,and 36%,respectively. In group B, triangular-shaped, trapezoidal-shaped, and irregular-shaped foramen accounted for 51%,17%,and 26%,respectively.The distribution of triangular-shaped, trapezoidal-shaped, and irregular-shaped foramen was compared between groups A and B, and the difference was recorded as statistically significant (P < 0.05). Additionally, the difference in the distribution of triangular-shaped, trapezoidal-shaped, and irregular-shaped foramen in group A was found statistically significant (P < 0.05),while that of Group B was found statistically insignificant (P > 0.05).On a horizontal CT scan of the vertebra of group A, triangles, trapezoids, and irregularities accounted for 28%, 26%, and 47%, respectively. In group B, triangles,trapezoids,and irregularities accounted for 31%, 37%, and 30%, respectively. The difference in the distribution of the triangular-shaped and trapezoidal-shaped foramen in groups A and B was statistically insignificant (P > 0.05), while that of irregular-shaped was statistically significant (P < 0.05). Additionally, there was no statistical significance (P > 0.05) in the difference in the morphological distribution of triangular-shaped and trapezoidal-shaped foramen in group A, while that of irregular-shaped was found to be statistically significant (P < 0.05). Further, the difference in the morphological distribution of triangular-shaped, trapezoidal-shaped, and irregular-shaped foramen in group B was not statistically significant (P > 0.05).In general, about 8% of the vertebral body of BF has an osseous septum. In group A, 97% are single-holed while the remaining 3% are porous; in group B, those with single holes accounted for 76%, while the remaining 24% are porous. In groups A and B, the difference in the morphological distribution of single-holed and multi-holed T8, T11, T12, L1, L2, L4, and L5 vertebral bodies was statistically significant (P < 0.05). In group A, the difference in the distribution of single-holed and multi-holed L1 and L5 vertebral bodies was statistically significant (P < 0.05). Similarly, the difference in the distribution of single-holed and multi-holed T8, T11, T12, L1, L2, and L4 basivertebral foramen was statistically significant (P < 0.05). Conclusions In patients with osteoporosis, the incidence of vertebral Kummell’s disease can be associated with the morphological characteristics of the basivertebral foramen, as observed in the CT scan. Furthermore, the vertebral body with trapezoidal-shaped and irregular-shaped basivertebral foramen and boneless septum in the foramen is highly susceptible to Kummell’s disease.